Emission and Lubrication Performance of Hazelnut Oil as A Lubricant - KEVEN, Arzu; ONER, Cengiz (International Journal of Computational and Experimental Science and Engineering, 2023)
The aim of this study is to search the tribological and emission performances of hazelnut oil as a lubricant in one cylinder two-stroke gasoline engine and simulation-testing machine. The tribological and emission performances of mineral oil and hazelnut oil as lubricant were compared. In the experiments, simulation-testing machine and one cylinder two-stroke gasoline engine were used to determine the tribological performance of these two lubricants. The wears on the surfaces of cylinder were analyzed to examine the lubricant performances. In addition to lubrication performance, exhaust emissions of the lubricants were also measured. To observe the effects of different kinds of cylinder surface materials, TiN, CrN and gray cast iron coated cylinder surfaces were used in simulation testing machine. The wear as well as the soot formation on the cylinder surfaces increased when hazelnut oil was used as the engine lubricant. However, hazelnut oil exhibited good lubrication properties in simulation testing machine. When hazelnut oil was used, CO and HC emissions increased while CO2 emission decreased.